Produção e consumo de frutos zoocóricos em dois fragmentos florestais do oeste do Rio Grande do Norte, Brasil. - Torquato, Jânio Lopes (Universidade Federal Rural do Semi-Árido, 2015)
The availability of fleshy fruits in forest fragments is essential for the survival of many animal species. The disadvantage of small fragments to native wildlife is the decrease in fleshy fruits availability, especially in the period of food shortage. Together with the food shortage period there is an environmental factor, rainfall, which directly influences the production of fruits zoochorous, and consequently in the diet and survival of fauna. The goal of this study was to compare the production and consumption of fruits zoochorous in forest fragments in the western of Rio Grande do Norte state. The study took place in two forest fragments: Parque Nacional da Furna Feia PARNA Furna Feia (8.517ha) and Trilha dos Polinizadores TRIPOL (26ha), from June 2013 to July 2014. The data collection was done every 15 days in pre-established trails in forest fragments. The counting of ripe fruit zoochorous in forest fragments was done in two ways: estimation and absolute. The diet of the animals was analyzed by feces collected on the trails and screened in the ECOMOL/UFERSA lab. The frugivorous animals were recorded with the help of the trap camera and some Caatinga native fruit were placed in front camera. The data of rainfall were obtained from the National Institute of Meteorology INMET. In total, 270 individuals were recorded fruiting, 13 zoochorous specie and nine botanical families. Considering the 13 species recorded zoochorous, only 11 were fruitful, 10 in the rainy season. The accumulated abundance of ripe fruit registered at the TRIPOL (n = 36,494; 15.7 fruits/m²) was higher than in PARNA Furna Feia (n = 27 168; 3.7 fruits/m²). At TRIPOL, the species which produced more fruits were: Spondias tuberosa, Ziziphus joazeiro, Lantana camara, Tournefortia volubilis and Phoradendron affine. At PARNA Furna Feia, the species which produced more fruits were: Ziziphus joazeiro and Commiphora leptophloeos. The relationship between the abundance of zoochorous fruit and the precipitation was significant at TRIPOL (rs = 0.5438, p = 0.0041), but there was no significant relation at PARNA Furna Feia (rs = 0.1973, p = 0.3337). There was no significant relation between the abundance of zoochorous fruit and the number of seeds registered in the feces. In them, 666 seeds were registered at TRIPOL and 4.281 seeds at PARNA Furna Feia. Considering the total number of seed found in the feces, the species T. volubilis and Sideroxylon obtusifolium represented 55,2% and 72,2% of total seed, respectively in each fragment analyzes. The animals recorded by the trap cameras consuming the fruit-baits in forest fragments were Tupinambis merianae, Ameiva ameiva, Turdus rufiventris, Mimus saturninus, Coereba flaveola, Cyanocorax cyanopogon, Cerdocyon thous and Callithrix jacchus. Cerdocyon thous and Cyanocorax cyanopogon were the two species which most consumed the fruit-baits of Copernicia prunifera and Cereus jamacaru, respectively. The species C. thous and C. cyanopogon can be important seed dispersers in forest fragments of the Caatinga. The fruits of species T. volubilis and S. obtusifolium are important food source for fauna, especially S. obtusifolium which offers ripe fruit during fleshy fruit shortage period
Production and consumption of fruits zoochorous in two forest fragments in the west of Rio Grande do Norte, Brazil.
Keywords: Fruit production; Forest fragments; Fleshy fruits; Caatinga; Precipitation rainfall; Fruticultura; Fragmentos florestais; Frutos carnosos; Caatinga; Precipitação pluviométricas; CIENCIAS BIOLOGICAS::ECOLOGIA